2014
DOI: 10.1021/bm501051t
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organized ECM-Mimetic Model Based on an Amphiphilic Multiblock Silk-Elastin-Like Corecombinamer with a Concomitant Dual Physical Gelation Process

Abstract: ABSTRACT. Although significant progress has been made in the area of injectable hydrogels for biomedical applications and model cell niches, further improvements are still needed, especially in terms of mechanical performance, stability and biomimicry of the native fibrillar architecture found in the extracellular matrix (ECM). This work focuses on the design and production of a silk-elastin-based injectable multiblock co-recombinamer that spontaneously forms a stable physical nanofibrillar hydrogel under phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
140
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(148 citation statements)
references
References 56 publications
(101 reference statements)
6
140
1
1
Order By: Relevance
“…This result highlights that both types of ELR hydrogels are very stable when implanted subdermally in vivo , even when the hydrogel network is only stabilised via non‐covalent interactions, which is the case of the SELR. This is in good agreement with previous findings for this type of recombinamer in vitro (Fernandez‐Colino et al, ) and suggests that additional biodegradation domains should be included in the amino acid sequence of the ELRs if a temporary implant is needed. However, the good stability over time observed here is relevant for both tissue‐engineering applications and for the development of drug‐delivery systems because the formation of a stable system could be crucial for achieving the long‐lasting effects required in many of these applications.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This result highlights that both types of ELR hydrogels are very stable when implanted subdermally in vivo , even when the hydrogel network is only stabilised via non‐covalent interactions, which is the case of the SELR. This is in good agreement with previous findings for this type of recombinamer in vitro (Fernandez‐Colino et al, ) and suggests that additional biodegradation domains should be included in the amino acid sequence of the ELRs if a temporary implant is needed. However, the good stability over time observed here is relevant for both tissue‐engineering applications and for the development of drug‐delivery systems because the formation of a stable system could be crucial for achieving the long‐lasting effects required in many of these applications.…”
Section: Resultssupporting
confidence: 92%
“…The resulting ELR‐cell suspensions were then injected subcutaneously in mice and hydrogels were formed instantaneously, as reported previously in vitro (Fernandez‐Colino et al, ; Gonzalez de Torre et al, ), and confirmed by the observation of a protuberance under the skin of the animals, which was not seen when PBS alone was injected. This is also in good agreement with previous in vitro studies regarding the gelation kinetics of SELRs (Fernandez‐Colino et al, ) and ELR‐CFCGs (Gonzalez de Torre et al, ). In the first case, a rapid gelation process was observed by rheological measurements upon increasing the temperature above the Tt, whereas for chemically cross‐linked hydrogels, these were formed in a few seconds upon mixing ELR‐azide and ELR‐cyclooctine solutions, as observed macroscopically.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…ELPs exhibit lower critical solution temperature (LCST) behavior; they are soluble below the LCST and form a coacervate, or a dense polymer-rich liquid phase, above the LCST. The Rodríguez-Cabello group has utilized the LCST behavior of ELPs to facilitate hydrogel formation of ELP-fusion proteins [9,10]. In addition, spherical structures of ELPs have been triggered by the thermo-responsive behavior [11].…”
Section: Structural Domainsmentioning
confidence: 99%
“…Such properties are maintained when GAGAGS motifs are engineering along an ELR molecule, giving rise to so-called SELR (silk-elastin like recombinamer). Many SELR-based hydrogels have been reported in the literature [94][95][96][97] and some of them have been successfully explored for drug-delivery purposes. [98][99][100][101] Indeed, the utility of SELRs has been explored in both the field of drug delivery and for the delivery of viral vectors.…”
mentioning
confidence: 99%